Impact of infiltrative growth on the outcome of patients with undifferentiated pleomorphic sarcoma and myxofibrosarcoma. Issue 6 (29th June 2014) - Iwata, Shintaro; Yonemoto, Tsukasa; Araki, Akinobu; Ikebe, Dai; Kamoda, Hiroto; Hagiwara, Yoko; Ishii, Takeshi
<x xml:space="preserve">Abstract</x> Background and Objectives Infiltrative growth, frequently observed in undifferentiated pleomorphic sarcoma (UPS) and myxofibrosarcoma (MFS), is often associated with a positive surgical margin as well as a local failure. The purpose of our study was to determine whether the radiographic growth patterns were associated with the outcomes of patients with UPS and MFS. Methods We reviewed 89 patients diagnosed with UPS or MFS and underwent initial surgery at our institute between 1994 and 2011. Growth patterns were assessed radiographically on preoperative MRI. Clinicopathological factors were collected and uni‐ and multivariate analyses were performed for survival. Results Infiltrative growth was observed in 21 patients (24%), which correlated with superficial tumors and positive surgical margin. Infiltrative growth correlated with poor disease‐specific and distant failure‐free survivals relative to non‐infiltrative growth. Multivariate analysis confirmed that these factors remained as significant factors. Patients with non‐infiltrative tumors resected inadequately exhibited slightly more favorable local control with postoperative radiotherapy, although no clinical benefit was seen for those with infiltrative tumors. Conclusions Infiltrative growth was an adverse prognostic factor for not only local control, but also disease‐specific and metastasis‐free survival in patients with UPS and MFS. Radiotherapy could not salvage inadequately resected infiltrative tumors. J. Surg. Oncol. 2014 110:707–711. © 2014 Wiley Periodicals, Inc.